Hypoxia-inducible factor 1α predicts recurrence in high-grade soft tissue sarcoma of extremities and trunk wall. Issue 10 (12th April 2017) - Nyström, H; Jönsson, M; Werner-Hartman, L; Nilbert, M; Carneiro, A
Abstract : Background and aim: Sarcomas are of mesenchymal origin and typically show abundant tumour stroma and presence of necrosis. In search for novel biomarkers for personalised therapy, we determined the prognostic impact of stromal markers, hypoxia and neovascularity in high-grade soft tissue leiomyosarcoma and pleomorphic undifferentiated sarcoma. Method: We evaluated CD163, colony-stimulating factor (CSF)-1, CD16 and hypoxia-inducible factor 1 (HIF-1)α using immunohistochemical staining and assessed microvessel density using CD31 in 73 high-grade leiomyosarcomas and undifferentiated pleomorphic sarcomas of the extremities and the trunk wall. The results were correlated to metastasis-free and overall survival. Results: Expression of HIF-1α was associated with the presence of necrosis and independently predicted shorter metastasis-free survival (HR 3.2, CI 1.4 to 7.0, p=0.004), whereas neither expression of the stromal markers CD163, CD16 and CSF-1 nor microvessel density was prognostically relevant in this series. Conclusions: There is increasing evidence for the prognostic role of hypoxia in high-grade soft tissue sarcoma, and these data suggest that HIF-1α expression represents a candidate prognostic biomarker for clinical application in high-grade leiomyosarcoma and undifferentiated pleomorphic sarcoma.